Multimedia distribution of polycyclic aromatic hydrocarbons in the Wang Lake Wetland, China - Shi, Changhe; Qu, Chengkai; Sun, Wen; Zhou, Jingzhe; Zhang, Jiawei; Cao, Yu; Zhang, Yuan; Guo, Jiahua; Zhang, Jiaquan; Qi, Shihua (Environmental pollution (1987), 2022)
The Wang Lake Wetland is a highly valued area that is protected due to its high biodiversity. The wetland has a complicated hydrological regime and is subject to frequent human disturbance. We hypothesize that fluctuating hydrology and human activities have varied contributions to the temporal and spatial variations of polycyclic aromatic hydrocarbons (PAHs) in the wetland. Soil (SS), sediment (SD), and water, to acquire dissolved phase (DP) and suspended particulate matter (SPM), samples were collected from eight locations during low- and high-flow periods to elucidate multimedia phase distribution and transport of PAHs. Following the onset of the rainy season, the concentration of SPM-associated PAHs increased significantly, while the DP PAHs remained stable. Individual PAH ratios showed that, although pyrogenic sources are common, petrogenic derived compounds are the main source of PAHs in the Wang Lake Wetland. During the high-flow period, the empirical values for logarithms of the organic carbon-normalized partition coefficients (log KOC) of individual PAH-congeners were lower than the corresponding field-observed log KOC values from the SPM-DP and SD-DP systems, reflecting the complexity in evaluating multi-phase PAH partitioning. During the high-flow period, temperature-driven changes may have changed the sediment from a sink to a source for some high molecular weight PAHs. It was determined that human activities governed the PAH loading in the low-flow period, whereas during high-flow conditions, increased rainfall, higher temperatures, and fishery activity are the main factors controlling PAH input to the Wang Lake Wetland. [Display omitted] •There is high spatial variability of PAH concentrations within the Wang Lake Wetland.•Suspended particle-associated PAHs increased with increased rainfall and temperature.•PAH partition in the multimedia system is in a dynamic state.•Human activity had a greater impact on PAH loading during a low-flow period.•Hydro-meteorological factors governed PAH input during the high-flow period.